2020
DOI: 10.3390/v12121387
|View full text |Cite
|
Sign up to set email alerts
|

Maize AKINβγ Proteins Interact with P8 of Rice Black Streaked Dwarf Virus and Inhibit Viral Infection

Abstract: Rice black streaked dwarf virus (RBSDV) is an important agent causing maize rough dwarf disease, whereas the host factors responding to RBSDV infection are poorly understood. To uncover the molecular interactions between RBSDV and maize, a yeast two-hybrid screen of a maize cDNA library was carried out using the viral P8 protein as a bait. ZmAKINβγ-1 and ZmAKINβγ-2 (βγ subunit of Arabidopsis SNF1 kinase homolog in maize) possessing high sequence similarities (encoded by two gene copies) were identified as inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The study of protein–protein interaction (PPI) through TEAs in protoplasts can also bring crucial information to decipher kinase signaling in plant cells ( Pecher et al, 2014 ; Cheng et al, 2015 ; Liu et al, 2017 ; Ye et al, 2019 ; Li et al, 2020 ; Takahashi et al, 2020 ), the activation and interaction of TFs ( Pecher et al, 2014 ; Liu et al, 2018 ; Ye et al, 2019 ), or even the interaction between immune receptors and co-receptors ( Halter et al, 2014 ; Yeh et al, 2015 ; Fliegmann et al, 2016 ; Gong et al, 2019 ; Li et al, 2019 ).…”
Section: Protoplasts As Tools In Biomolecular Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of protein–protein interaction (PPI) through TEAs in protoplasts can also bring crucial information to decipher kinase signaling in plant cells ( Pecher et al, 2014 ; Cheng et al, 2015 ; Liu et al, 2017 ; Ye et al, 2019 ; Li et al, 2020 ; Takahashi et al, 2020 ), the activation and interaction of TFs ( Pecher et al, 2014 ; Liu et al, 2018 ; Ye et al, 2019 ), or even the interaction between immune receptors and co-receptors ( Halter et al, 2014 ; Yeh et al, 2015 ; Fliegmann et al, 2016 ; Gong et al, 2019 ; Li et al, 2019 ).…”
Section: Protoplasts As Tools In Biomolecular Studiesmentioning
confidence: 99%
“…In PCA ( Figure 2C ), one of the studied proteins is fused with the amino-terminal part and the other one with the carboxy-terminal part of a fluorescent protein, such as YFP or mCherry, for BiFC ( Pecher et al, 2014 ; Cheng et al, 2015 ; Li et al, 2020 ) or a luciferase enzyme, such as the firefly luciferase, for SLC ( Chen et al, 2008 ; Cheng et al, 2015 ; Gong et al, 2019 ). In BiFC, when the two proteins interact, the combination of the two parts of the fluorescent protein restores the fluorescence enabling the visualization and the spatial location of protein complexes.…”
Section: Protoplasts As Tools In Biomolecular Studiesmentioning
confidence: 99%
“…P8 is reported to localize to the nucleus of insect vector and plant cells and repress transcription in tobacco suspension cells (Liu et al, 2007a). Our previous study revealed that P8 interacted with maize AKINβγ, the regulatory subunit of the SNF1-related protein kinase 1 (SnRK1) complex, thus regulating primary carbohydrate metabolism of host plant in response to RBSDV infection (Li et al, 2020). In addition, SP8 encoded by southern rice black-streaked dwarf virus, a closely related fijivirus, was reported to interfere with the dimerization of auxin response factor 17 of rice thus disturbing the auxin signaling pathway and facilitating virus infection (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rad GDP dissociation inhibitor alpha was identified as a host susceptibility factor for RBSDV resistance. βγ subunit of Arabidopsis SNF1 kinase (ZmAKINβγ-1) homolog in maize and ZmAKINβγ-2, two proteins with high sequence similarities, play important roles in the defense against RBSDV infection by regulating the primary carbohydrate, metabolism [ 10 ]. By comparative genomic analysis of the resistant inbred line (X178) and susceptible line (Ye478), Zea mays Eukaryotic Initiation Factor 4E ( ZmeIF4E ) was considered as a candidate gene for MRDD resistance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%